PENGARUH AKSESIBILITAS INTERNET TERHADAP LUARAN PASAR KERJA DI INDONESIA - Mahalli, Fina Nidaul; Pratomo, Devanto Shasta (Journal of Development Economic and Social Studies, 2024)
After the Covid-19 pandemic, internet usage has increased dramatically. However, the impact of internet accessibility on the job market is still a circle in academic circles. There are those who argue that internet accessibility can improve labor market performance by reducing information distortions and increasing workers' skills. However, there are also those who argue that internet accessibility can hamper labor market performance due to a skills bias, where workers who are less skilled with routine tasks tend to be left out in the digitalization era. Therefore, this study aims to evaluate the extent to which internet accessibility influences the labor market in Indonesia using the Fixed Effect Model (FEM) method and Central Bureau of Statistics (BPS) data for 2010-2020. The results show that in general, the internet tends to improve the performance of the labor market in Indonesia with a positive effect on wage rates and the proportion of workers in the formal sector, and a negative effect on the Open Unemployment Rate (TPT). This study suggests that the internet can increase productivity and income as well as facilitate access to information on the labor market in Indonesia.